2016
DOI: 10.1186/s40064-015-1502-9
|View full text |Cite
|
Sign up to set email alerts
|

Are we over treating Pineal Parenchymal tumour with intermediate differentiation? Assessing the role of localised radiation therapy and literature review

Abstract: Pineal Parenchymal tumour with intermediate differentiation (PPTID) is a rare disorder, first classified by World Health Organisation in 2000. There are very few published data available and optimal management is yet to be determined. Management has varied from surgery alone to craniospinal radiotherapy with or without chemotherapy. We present our experience of PPTID treated with radiotherapy alone. We conducted a retrospective review of patients who were diagnosed with PPTID and treated with radiation therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…The study of 30 patients of pineal tumors demonstrated a link between radiation dose and survival time. 7 In this patient, as the first case report of PPTID in our hospital, the total tumor removal was hard to achieve due to the tumor location and invasion toward the surrounding areas. This patient will be monitor with a brain and spine MRI scan for residual lesions and recurrence which will be presented at a multidisciplinary conference.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The study of 30 patients of pineal tumors demonstrated a link between radiation dose and survival time. 7 In this patient, as the first case report of PPTID in our hospital, the total tumor removal was hard to achieve due to the tumor location and invasion toward the surrounding areas. This patient will be monitor with a brain and spine MRI scan for residual lesions and recurrence which will be presented at a multidisciplinary conference.…”
Section: Discussionmentioning
confidence: 80%
“…Prognostic factors were grading of tumor, neuraxis spread, and extent of resection. 7,11 Watanabe et al, 9 reported on patients with PPTID with cerebrospinal dissemination who received 36Gy of CSI and adjuvant chemotherapy in the management of CSF dissemination. The total radiation dose >50Gy and chemotherapy may be an effective treatment for PPTID with dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, craniospinal irradiation would be a logically acceptable approach for patients with leptomeningeal dissemination. 7 Schild et al reported on 30 patients with pineal tumors and found a relationship between the radiation dose and survival time in patients with PPT. 25 They reported that patients receiving a higher dose (> 50 Gy) of radiation had a significantly improved 3-year survival rate compared with those receiving a lower dose (94% vs 56%, respectively).…”
Section: Radiotherapymentioning
confidence: 99%
“…Also, craniospinal irradiation would be a useful treatment for PC patients with leptomeningeal dissemination. 7 Gomez et al reported a patient in whom PC was diagnosed by biopsy and who was treated with local irradiation. Ten years after treatment, the patient showed craniospinal CSF dissemination, and histological examination of the recurrent tumor revealed a pathologically malignant change (MIB-1 index 10%-15%), and a diagnosis of PPTID was established.…”
Section: Leptomeningeal Disseminationmentioning
confidence: 99%